Integrated multisource estimates of mortality for Thailand in 2005 - Byass Peter (Population Health Metrics, 2010)
Abstract Estimates of mortality in Thailand during 2005 have been published, integrating multiple data sources including national vital registration and a national follow-up cluster sample, covering both deaths in health facilities (approximately one-third) and elsewhere. The methodological challenge is to make the best use of the existing data, supplemented by additional data that are feasible to obtain, in order to arrive at the best possible overall estimates of mortality. In this case, information from the national vital registration database was supplemented by a verbal autopsy survey of approximately 2.5% of deaths, the latter being used to validate routine cause-of-death data and information from medical records. This led to a revised national cause-specific mortality envelope for Thailand in 2005, amounting to 447,104 deaths. However, difficulties over standardizing verbal autopsy interpretation may mean that there are still some uncertainties in these revised estimates.